G309 A tale of two brothers – case report and literature review of treatment for adenosine deaminase 2 (DADA2). (25th October 2020) - Close, R; Armon, K
Abstract : Background: Two brothers, both with past history of early-onset strokes (bilateral thalamic infarcts aged 6 years in one and left mid brain infarct aged 4 in other) were referred to the neurology and genetics service. Investigation releveled iron refractory anaemia (subsequently managed by haematology) and isodisomy for chromosome 22. Both made a good neurological recovery and were commenced on daily aspirin. Gene CECR1 was considered but dismissed due to no reported myalgia, fever or skin rash. Five years after initial referral whole genome sequencing revealed a homozygous mutation in the adenosine deaminase 2 gene (CECR1). Both brothers were diagnosed with adenosine deaminase 2 deficiency (DADA2) and referred to paediatric rheumatology. Review of previous investigations revealed persistently raised inflammatory markers. Hepatosplenomegaly was present in both and lymphadenopathy and ear symptoms in younger brother on initial rheumatology review. Mutations in the CECR1 gene prevent it correctly encoding the enzyme Adenosine Deaminase 2. This is a growth factor for endothelial cells and promotes the differentiation of M2 macrophages. Deficiency results in decreased vascular integrity, a predominance of proinflammatory macrophages and perivascular inflammation medicated by tumour necrosis factor (TNF). Methods: A literature review was carried out to determine evidence of treatment for this rare condition. Results: DADA2 is currently extremely rare with only 200 cases reported in the literature. Small studies have found anti-TNF medication to be beneficial in reducing glucocorticoid use and preventing further neurological events. There are case reports of successful allogeneic hematopoietic stem-cell transplantation but concerns remain that associated vascular problems may increase the risk of serious side effects. Conclusion: Following literature review an internal funding request for Adalimumab was accepted and both boys commenced anti-TNF treatment. We present a case of two brothers with this recently discovered monogenic systemic vasculopathy, now recognised to show huge clinical diversity even among family members with identical mutations. Immunodeficiency and haematological features are commonly reported but awareness across all specialties is needed. It is currently unknown how defects in a single gene results in these heterogeneous presentations. It is hoped that gene therapy will provide a cure for this condition in the future.